Identifying the hygroscopic properties of fine aerosol particles from diverse sources in urban atmosphere and the applicability in prediction of cloud nuclei. (1st April 2023) - Ren, Jingye; Zhang, Fang; Chen, Lu; Cao, Gang; Liu, Mengyu; Li, Xue; Wu, Hao; Cheng, Yiling; Li, Zhanqing
Abstract: Aerosols hygroscopicity is generally differentiating for particles among various sources, leading to complex effects on visibility impairment and cloud formation. However, the hygroscopicity of aerosol particles from diverse sources is not yet fully understood. Here, combining field observations at an urban site in Beijing and a positive matrix factorization model, we identified aerosols hygroscopicity of six different sources, nucleation, traffic, cooking, aging primary, residential heating, and regional secondary, which corresponds to hygroscopic growth factors (Gfs) of 1.23, 1.15, 1.17, 1.44, 1.48, and 1.47, respectively at relative humidity of 90%. On polluted days, Gf values of particles for the accumulation-mode particles were higher than that under clean conditions. This is largely due to the hygroscopic sources represented by aged and secondary processes showed the dominant role in aerosol population. While on clean days, the Gfs of 40-nm particles showed larger values, that is closely associated with the photochemical-nucleation-sourced particles. By further applying the Gfs together with aerosol spectrum to predict cloud nuclei concentration (CCN), we find the predicted and observed CCN number concentration are well correlated at typical supersaturation in cloud. The study further reveals the dominant roles of secondary processes, contributing up to 90% of the total cloud nuclei. Primary particles from traffic/cooking activities contributed only ∼5%, although they account for 30–40% of the total particle number concentrations in urban Beijing during the studied period. The results indicate the source apportionment of Gfs can well interpret the variation in hygroscopicity of aerosols under different atmospheric conditions and evaluate their effects on cloud formation. Highlights: The hygroscopicity of aerosol particles from specific sources was identified in winter of Beijing. The hygroscopic growth factors together with aerosol spectrum could predict N CCN well at typical supersaturation in cloud. Secondary sources were the dominant contributor to the total cloud nuclei, while primary particles contributed less.